Mothers' Knowledge Before and After Counseling on Child Immunization using Learning Video Media - Herliana, Herliana; Fitria, Rahmah (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
The decline in infant mortality remains a concern, even though it has decreased over the past five decades. Some causes of death can be prevented through immunization. The success of immunization counseling depends on effective and efficient methods.This study aimed to determine the difference in mothers' knowledge levels before and after counseling on child immunization using learning video media. The research used a quasi-experimental design with a one-group pre-test post-test approach. The study population consisted of mothers who attended immunization counseling at the Puskesmas.The results showed that the average mother's knowledge before counseling was 65 (SD = 0.5), categorized as "sufficient." After counseling, the average increased to 83 (SD = 0.6), categorized as "good." The Wilcoxon Signed Ranks test showed a significance value of 0.000, indicating a significant difference before and after counseling. In conclusion, counseling using learning video media effectively improves mothers' knowledge about child immunization. Health workers are encouraged to provide regular and creative health education using the most effective media to enhance mothers' understanding of immunization.